Tirofiban-Induced Thrombocytopenia Occurring with Crohn’s Disease - Toni Ibrahim; Fady El Karak; Assem Araji; Elie El Rassy (Case Reports in Cardiology)
A 69-year-old man, with severe refractory Crohn’s disease, presented with acute coronary syndrome that required angioplasty. He developed severe tirofiban-induced thrombocytopenia (TIT) heralded by type I allergic reaction that required steroids and a combination of antihistamine H1 and antihistamine H2 for symptomatic management. The thrombocytopenia spontaneously resolved uneventfully in 48 hours thereafter. This case report suggests a possible association between TIT and inflammatory bowel disease. Therefore, strict monitoring of the platelet count is required in patients who develop allergic reactions to tirofiban.